PERANCANGAN PERAWATAN MESIN BLOCK MILL DENGAN METODE RELIABILITY CENTERED MAINTENANCE II (Studi Kasus : PT. The Master Steel MFC) - Oktavia Kusuma Negara (2021)
The coil is one of the final products in the form of a Wire Rod (steel wire rod) with a round cross-section packaged in the form of a coil made of billet steel. To produce Wire Rod using one machine, the Block Mill machine. Block Mill Machine, which functions to reduce the material from the finished product, is formed with great precision, including the accuracy of size, shape, and visible properties. Based on observations, one of the often used machines and often experiences downtime is the Block Mill machine. Block Mill machines have a vital role in producing products. To solve this problem, it is necessary to plan an optimal maintenance policy so that the production process remains in optimal condition using the Reliability Centered Maintenance (RCM) II method. The RCM II method can determine the factors and effects of system failure, determine activity and maintenance intervals. There are several stages of data processing, namely FMEA calculation, RCM II Decision Worksheet, calculation of TTF and TTR parameters, determination of appropriate distribution, calculation of MTTF and MTTR, calculation of maintenance time intervals, comparison of reliability after and before Preventive Maintenance. In the research, it is proven that with the formulation of RCM II, the results of the maintenance intervals are on Stand 18 109 hours, Stand 23 with a treatment interval of 991 hours, Stand 25 with a maintenance interval of 853 hours, and for Stand 26 with a treatment interval of 90 hours, it can increase the reliability to 81% for Stand 18, 57% for Stand 23, 52% for Stand 25, and 87% for Stand 26